Endurance Swimming Is Related to Summer Lake Survival of Rainbow Trout in a Warm Lake with Avian Piscivores - Christine E. Verhille; Anthony P. Farrell (Fishes, 2023)
Fitness of fish is assumed to be influenced by locomotion performance, but empirical evidence linking swimming capacity to survival in nature remains sparse. Poor triploid (3N) fish aerobic swimming performance in conjunction with production of sibling diploid (2N) and 3N populations of genetically identical origin to minimize variability among compared populations make 3N trout an informative system to test hypotheses about fitness consequences of fish locomotion. Here, we ask if reduced survival of 3N relative to 2N trout in natural ecosystems during periods of high temperature relate to a lower aerobic swimming capacity and aerobic scope of 3N compared with 2N conspecifics. Three-yearly cohorts of conspecific 2N and 3N hatchery-reared, yearling rainbow trout were ranked for swimming endurance, externally marked for their endurance quantile, and then stocked into two lakes as yearlings to quantify their survival in the wild over summer as a function of ploidy, temperature and endurance; all while tracking temperature and depth habitat utilization via telemetry. As expected, 3N swimming endurance was lower than that of 2N, but with considerable individual overlap. Aerobic swimming endurance, especially for 3N, was predictive of summer survival in a warm lake where piscivorous birds potentially exerted high predation pressure, resulting in low fish survival. This empirical evidence of a connection between swimming endurance and fitness provides support for long held assumptions of this relationship and could inform future sport fishing stocking industry practices to match fish strains to ideal habitats.